Risk Factors in Children with Congenital Anomalies of Kidney and Urinary Tract - Nuran Çetin; Aylin Gençler (Galenos Publishing House, 2020)
INTRODUCTION: Congenital anomalies of kidney and urinary tract (CAKUT) constitute the most important cause of chronic kidney disease in children. There is insufficient data on the risk factors of these anomalies. In this study, it was aimed to investigate risk factors in children with CAKUT. METHODS: Patients with CAKUT and healthy children as a control group were included. Weight gain of mother during pregnancy, body mass index before pregnancy, the use of cigarette, folic acid, iron and drug of mothers, gestational week, birth weight children were investigated. RESULTS: A 142 patients and 124 children without anomalies were included in this study. The most frequent anomaly was vesicoureteral reflux (n=39), and the second most common was ureteropelvic junction obstruction (n=30). The frequency of having with low birth weight was higher in children with CAKUT than the control group (n=22 [15.5%], n=12 [9.67%], p=0.045, respectively). While 18.3% of the mothers were obese in the patient group, this rate was 5.6% in the control group (p=0.006). In logistic regression analysis, a statistically significant relationship was found between obesity and CAKUT (Odds ratio: 1.54, confidence interval: 1.122-1.981, p=0.021). The rate of mothers who gained excess weight during pregnancy was higher in the patient group (17.6% [n=25], 11.3% [n=14], p=0.032, respectively). There was a significant relationship between overweight gain during pregnancy and the presence of CAKUT (Odds ratio: 1.15, confidence interval: 1.075-1.453, p=0.041). DISCUSSION AND CONCLUSION: Maternal obesity before pregnancy and excess weight gain during pregnancy can be a risk factor for CAKUT. Early investigation of these children in terms of CAKUT can be useful in early diagnosis and treatment planning.